Wife-Beating Endorsements Among African Youths: Current Prevalence and Predictors in 14 Sub-Saharan African Countries From 2015 to 2021 - Ola, Bamidele Emmanuel (Violence against women, 2024)
This study investigates the prevalence and predictors of wife-beating endorsements among never-in-union male and female African youths, aged 15–24 years. Demographic and Health Survey data from 14 Sub-Saharan African countries (female = 55,387; male = 29,128) were analyzed using multiple logistic regression analyses. Approximately 37% of male and 42% of female African youths justified wife-beating, ranging from Mali (female = 71.1%, male = 58.7%) to Malawi (female = 21.4%, male = 22.3%). Young age, low education, limited Internet access, poverty, and rural residence were commonly associated with acceptance. Eliminating violence against women in Africa requires timely and adequate interventions.